2017
DOI: 10.1155/2017/1683979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Saturation on the Diffusion/Adsorption of 22Na and Cesium onto the Callovo-Oxfordian Claystones

Abstract: The diffusion and adsorption behaviors of sodium and cesium were investigated in the Callovo-Oxfordian claystones (France) under unsaturated conditions. Through-, out-, and in-diffusion laboratory experiments were performed on intact and compacted samples. These samples were partially saturated using an osmotic method for imposed suction up to 9 MPa. This specific technique enabled us to obtain water saturation degree ranging from 81% to 100% for intact samples and from 70% to 100% for compacted materials. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For instance, the relative hydraulic conductivity and the specific storage coefficient decreased strongly with decreasing saturation of the samples. Savoye et al (2010Savoye et al ( , 2012Savoye et al ( , 2014Savoye et al ( , 2017 investigated diffusion of a water tracer and of anions and cations through partially saturated samples of Callovo-Oxfordian claystone as well as through compacted clays with variable clay content. All diffusion coefficients D e were clearly reduced in partly saturated samples compared to fully saturated ones.…”
Section: Influence Of Partial Saturationmentioning
confidence: 99%
“…For instance, the relative hydraulic conductivity and the specific storage coefficient decreased strongly with decreasing saturation of the samples. Savoye et al (2010Savoye et al ( , 2012Savoye et al ( , 2014Savoye et al ( , 2017 investigated diffusion of a water tracer and of anions and cations through partially saturated samples of Callovo-Oxfordian claystone as well as through compacted clays with variable clay content. All diffusion coefficients D e were clearly reduced in partly saturated samples compared to fully saturated ones.…”
Section: Influence Of Partial Saturationmentioning
confidence: 99%
“…Diffusion experiments have shown that anion diffusion is more strongly reduced than cation diffusion in the presence of water unsaturated conditions. Numerous processes were put forward to explain this observation, including differences in diffusion pathway disruptions among cations, anions, and neutral molecules. Our study emphasizes that mechanisms taking place at the surface, such as formation and immobilization of ion pairs, may also be partly responsible for the observed differences between anion and cation diffusion property evolution with desaturation. As for water diffusion, our study corroborates the fact that a limited desaturation is not responsible for a decrease of water molecules self-diffusion coefficient.…”
Section: Resultsmentioning
confidence: 77%
“…Note that Churakov (2013) reports also significant increase of self-diffusion coefficient of water for similar conditions. This behavior combined with data obtained from other clayey materials (Savoye et al, 2017) allow us to explore the waterenhanced mobility assumption. This can be also justified due to the very low Rd values measured for ions under unsaturated conditions compared to full saturated one.…”
Section: Effect Of Water Saturation On Tracer Diffusive Ratementioning
confidence: 95%
“…They showed that the De value decreased by 22% when saturation decreased from 100% to 93.3%. Savoye et al developed an original approach to perform diffusion experiments under partially saturated conditions in illite-sand mixtures (Savoye et al, 2014) and in Callovo-Oxfordien claystones, envisaged to host a French disposal facility for high-and intermediate level longlived radioactive waste (Savoye et al, 2017(Savoye et al, , 2012(Savoye et al, , 2010. The osmotic method was used to control the partial saturated conditions of the clayey samples over the duration of diffusion experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation